2020
DOI: 10.1515/tnsci-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Chinese and western medicine for acute guillain-barré syndrome treatment

Abstract: AbstractIntroductionGuillain-Barré syndrome (GBS) is a worldwide demyelinating polyradiculopathy and polyneuropathy. Currently, there is no specific drug for GBS, and established treatment is generally based on immune-modulating treatment with plasma exchange or intravenous immunoglobulin in combination with supportive care. This study aimed to investigate the efficiency of integrated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…At present, there is no specific drug for GBS, and established treatment is generally based on immunemodulating treatment with plasma exchange or intravenous immunoglobulin in combination with supportive care (11)(12)(13). Recently, some novel drugs have been reported to be potentially effective, such as memantine, bifidobacterium, gabapentin, etc.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no specific drug for GBS, and established treatment is generally based on immunemodulating treatment with plasma exchange or intravenous immunoglobulin in combination with supportive care (11)(12)(13). Recently, some novel drugs have been reported to be potentially effective, such as memantine, bifidobacterium, gabapentin, etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, effective supporting therapeutic strategies for GBS, such as traditional Chinese medicine (TCM) approaches, are still urgently required. Previous research has suggested that the integration of an empirical TCM strategy and the current treatment could have a better effect on GBS (Yang and Zhao 2020).…”
Section: Introductionmentioning
confidence: 99%